Coupled systems theory, models, and applications in engineering - Geiser, Jürgen (Chapman & Hall/CRC numerical analysis and scientific computing series, 2014)
"In this monograph, we describe the theoretical and practical aspects of solving complicated and coupled models in engineering with analytical and numerical methods. Often such models are so delicate such that we need e cient solver methods to overcome the di culties. Therefore, we discuss the ideas of solving such multiscale and multiphysics problems with the help of splitting multiscale methods. We describe analytical and numerical methods in time and space for evolution equations that arise from engineering problems and their applications. The book gives an overview of coupled systems in applications: Coupling of separate scales: Micro- and macroscale problems (coupling separate scales) Coupling of multiple scales: Multiscale problems (homogenization of the scales) Coupling of logical scales: Multiphysics problems (multiple physical processes on a logical scale) The mathematical introduction describes the analytical and numerical methods which are used with respect to their e ectiveness, simplicity, stability and consistency. The algorithmic part discuss the methods, which are discussed with respect to their capability of solving problems in real-life applications to engineering tasks. In the experiment part, we present engineering problems with respect to the used code* and implementation. The idea is to consider a theoretical approach to coupled systems with novel and specialized single and multiple scale methods. We include iterative and embedded discretization schemes, which are used in multiphysics and *MATLAb an Simulink are registered trademarks of the The MathWorks, Inc"..